Testing the Reaction of Spanish Exchange Market with the Use of Event Study - Ulmann, Kamila; Roszkowski, Filip (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis: The aim of the article is to examine the significance of the reaction of stock exchange investors in that country to the publication of information about the reintroduction of border controls in order to limit the movement of people, especially foreigners. The article discusses issues related to economics and behavioral finance, paying special attention to the irrationality of decisions, discussed by many authors, under the influence of various factors. Methodology: In the case of the empirical study, event analysis methodologies were applied, using abnormal and cumulative abnormal rates of return. Results of the research: The results of a detailed analysis of events, based on overnormative single-period logarithmic rates of return and cumulative over-normative single-period logarithmic rates of return for an event, showed an interesting case contradicting the thesis on irrationality of investor behavior in the capital market, while questioning the efficient market hypothesis.